Partai Politik Dan Moderasi Beragama Sebagai Pilar Demokrasi di Indonesia - Muhammad Ardhi Razaq Abqa (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
Indonesia is a large nation with a diversity and a lot of its society. In a multicultural society, there is a potential conflict among the nation's children who are at risk of splitting unity and unity. This kind of reality is often found in various democratic contestations in the election of regional chiefs (elections). Religious moderation becomes very important when in a process of democracies emerging identity politics which of course risk injuring democratic values. The purpose of this research is to discuss the effectiveness of religious moderation in realizing the democratic elections (regional election) and the function of political political parties in religious moderation as a pillar of democracy in Indonesia. The method used is research libraries. The conclusion of this research is the first, religious moderation is effective in establishing democratic elections, both political parties serve as a mobilizer for religious moderation to create a dignified and lasting democracy